2013
DOI: 10.1117/12.2006361
|View full text |Cite
|
Sign up to set email alerts
|

Defect detection in laser powder deposition components by laser thermography and laser ultrasonic inspections

Abstract: Laser Powder Deposition (LDP) techniques are being adopted within aerospace and automotive manufacturing to produce innovative precision components. Non-destructive techniques (NDT) for detecting and quantifying flaws within these components enables performance and acceptance criteria to be verified, improving product safety and reducing ongoing maintenance and product repair costs.In this work, software enabled techniques are presented for in-process analysis of NDT laser ultrasonic signals and pulsed laser t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In-line laser thermography testing involves shining a laser onto the surface of the WAAM part while it is being built. The laser heats the surface, causing it to emit infrared radiation [57]. A thermal imaging camera is then used to capture the emitted radiation and create a thermal image of the object.…”
Section: Laser Thermographymentioning
confidence: 99%
See 1 more Smart Citation
“…In-line laser thermography testing involves shining a laser onto the surface of the WAAM part while it is being built. The laser heats the surface, causing it to emit infrared radiation [57]. A thermal imaging camera is then used to capture the emitted radiation and create a thermal image of the object.…”
Section: Laser Thermographymentioning
confidence: 99%
“…A thermal imaging camera is then used to capture the emitted radiation and create a thermal image of the object. By analyzing the thermal image, it is possible to detect areas of the object that are hotter or cooler than others, which can indicate the presence of defects or inconsistencies in the WAAM part [31,57].…”
Section: Laser Thermographymentioning
confidence: 99%
“…Defect information is produced to identify processing errors and modify processing parameters in real time [ 77 ]. The use of LUT generating a Rayleigh wave in power direct energy (PDE) deposition metallic samples has been done for a small number of studies in which discontinuities between 150 and 500 were observed at a depth of up to 700 , which were considered surface or close to surface defects [ 78 ]. Another work reported and proved the possibility of using LUT generating a Lamb wave to detect the natural formatted [ 79 ] and artificial [ 80 ] defects inside a printed Ti6Al4V block.…”
Section: Ultrasonic Inspection and Evaluationmentioning
confidence: 99%
“…With the profile images (B-scans), the minimum detectable diameter was 0.725 mm for defects at a depth up to 0.7 mm . Further studies have been conducted applying ultrasonic testing (UT) for in situ monitoring [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%